A Chromogenic Probe for the Selective Recognition of Sarin and Soman Mimic DFP1. Issue 4 (1st August 2014) - El Sayed, Sameh; Pascual, Lluís; Agostini, Alessandro; Martínez-Máñez, Ramón; Sancenón, Félix; Costero, Ana M.; Parra, Margarita; Gil, Salvador
Abstract The synthesis, characterization and sensing features of a novel probe 1 for the selective chromogenic recognition of diisopropylfluorophosphate (DFP), a sarin and soman mimic, in 99:1 (v/v) water/acetonitrile and in the gas phase is reported. Colour modulation is based on the combined reaction of phosphorylation of 1 and fluoride‐induced hydrolysis of a silyl ether moiety. As fluoride is a specific reaction product of the reaction between DFP and the −OH group, the probe shows a selective colour modulation in the presence of this chemical. Other nerve agent simulants, certain anions, oxidant species and other organophosphorous compounds were unable to induce colour changes in 1. This is one of the very few examples of a selective detection, in solution and in the gas phase, of a sarin and soman simulant versus other reactive derivatives such as the tabun mimic diethylcyanophosphate (DCNP).